(untitled) (Studia Prawnicze / The Legal Studies, 1967)
The author intends to present certain influential factoirs of integration of six countries of Western Europe occuring within the European Economic Community on that part of legislation which is called private law in these countries. The Rome Treaity establishing the EEC does not provide systematic and complete unification of private law, it obliges, however, the EEC to try to bring closer the legislations of particular member-countries only within the regulations that are of concern to functioning of the Common Market. For this purpose is meant the institutional structure formed within the EEC besides known methods that have already been employed in (international relationships. The effecting of tasks charged upon the EEC lis -secured by the appropriate Cioramiunlity’is institutions, namely: Assembly, Council, Commission, and the Community’s Court. Of these bodies legal rights are vested in Commission and Council that are authorized to issue orders and directives, make decisions, and formulate instructions or opinions. Therefore, according to a particular situation, these organs can either make complete unification of legal regulations of member-countries by means of an enactment, or to conduce to their material unification with simultaneous maintenance of differences as regards the forms in which it is to be effected by means of the appropriate directives, or .finally, these bodies can confine themselves to convey to the concerned countries non-binding recommendations. In the author’s opinion, the analysis of the Treaty enactments leads to the conclusion that the cases they provide regarding issuing orders by the ’Council do not concern questions included in so called private law. As regards this problem, the directives will be the appropriate means to be used by the Council for rapproaehing legislations of particular countries. The volume of regulations in particular legislations which is to be the subject of rapprioachmenlt has been determined in the Treaty not very precisely, what has given in effect different standpoints in the doctrine. Practice proves that till now the Council gives rather flexible interpretation of the Treaty enactments. Further on, the author makes an analysis of Articles 100-102 of the Treaty that are fundamental for the EEC Council in his action for rapproachment of the member-countries legislations. In view of this analysis the author points out that the EEC bodies have been supplied with the appropriate means for attaining the rapproachment of particular member-countries laws in the determined area in consideration of various conditions under which this purpose is to foe effected. Article 100 of the Treaty gives attention to’ the scope of this action which may be defined as making a rapproachment a priori, and Article 101 provides situations in which certain repressive elements are allowed to be assigned to the rapproachment made by virtue of this article. On the other hand, the rights vested in the Community authorities due to Article 102 of the Treatise in consideration of circumstances that may occur in the future make possible to attain the rapproachment of laws of member-countries also pro futuro. Besides the mentioned methods for achieving unification of law within EEC, the Treaty provides ways for effecting the rapproachment of legislations in certain cases by means of an international agreement concluded by member-countries. (Art. 220). Further on, the author extensively discusses successful activities of EEC to be noted till now in the field of unification of law, as well as means used within this organization for securing the uniform interpretation of unified regulations. These questions lie with the Community’s Court of Justice which besides his function of controlling legality of legal and administrative decisions issued by EEC organs, and controlling that regulations of the Treaty are observed by member countries, has also to see to that all member-countries uniformly apply the legislative acts that have been unified so far. In the anther’s opinion, the nights vested in the Court by the Treaty are, however, too narrow to let it effectively counteract dezintegration trends in adjudication procedure in member-countries. In conclusion, the author states among ethers that the achievements of EEC in his activity so far for unifying so called private law is rather pour and in view of increasing political contradictions within the member-countries of Common Market to be recently observed it is not to be expected to make it soon more successful.